1999
DOI: 10.1152/ajpendo.1999.276.2.e278
|View full text |Cite
|
Sign up to set email alerts
|

Effect of short-term fasting on lipid kinetics in lean and obese women

Abstract: We evaluated whole body and regional adipose tissue lipid kinetics and norepinephrine (NE) spillover during brief fasting in six lean [body mass index (BMI) 21 ± 1 kg/m2] and six upper-body obese (UBO; BMI 36 ± 1 kg/m2) women. At 14 h of fasting, abdominal adipose tissue glycerol and free fatty acid (FFA) release rates were lower ( P = 0.07), but whole body glycerol and FFA rates of appearance (Ra) were greater ( P < 0.05) in obese than in lean subjects. At 22 h of fasting, glycerol and FFA Ra increased les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
104
2
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(118 citation statements)
references
References 29 publications
5
104
2
3
Order By: Relevance
“…Since insulin is the major regulator of basal adipose tissue lipolytic activity (19,20), the higher rates of nocturnal and postprandial lipolysis in our diabetic subjects compared with control subjects were due at least in part to resistance to the antilipolytic effects of insulin in adipose tissue. In fact, the diabetic subjects had higher lipolytic rates in spite of threefold greater plasma insulin concentrations compared with control subjects.…”
Section: Discussionmentioning
confidence: 87%
“…Since insulin is the major regulator of basal adipose tissue lipolytic activity (19,20), the higher rates of nocturnal and postprandial lipolysis in our diabetic subjects compared with control subjects were due at least in part to resistance to the antilipolytic effects of insulin in adipose tissue. In fact, the diabetic subjects had higher lipolytic rates in spite of threefold greater plasma insulin concentrations compared with control subjects.…”
Section: Discussionmentioning
confidence: 87%
“…10,11,29,37 In the absence of any significant increase in GH secretion obese patients in our study showed normal activation of lipolysis; this probably reflects the fasting-induced response of other contraregulatory hormones. 38 In this context, modification in IGF-I bioactivity brought about by fasting-induced changes in the most important binding proteins could play a major metabolic role. 39,40 In conclusion, short-term fasting does not stimulate mean GH concentration in obesity as well as in hypopituitary patients with severe GHD.…”
Section: Discussionmentioning
confidence: 99%
“…Local noradrenaline spillover from a subcutaneous adipose tissue bed does not change significantly between the overnight fasted state (14 h fast) and 22 h fast. 81 In contrast, there is increased noradrenaline spillover from adipose tissue associated with (and possibly causing) increased local blood flow 60-120 min after eating and after 72 h fasting. 64,82 In addition to acute effects on adipose tissue function, the SNS innervation appears to affect cell numbers.…”
Section: Innervation Of White Adipose Tissuementioning
confidence: 99%